A decrease of the butyrate-producing species Roseburia hominis and Faecalibacterium prausnitzii defines dysbiosis in patients with ulcerative colitis. Issue 8 (10th September 2013) - Machiels, Kathleen; Joossens, Marie; Sabino, João; De Preter, Vicky; Arijs, Ingrid; Eeckhaut, Venessa; Ballet, Vera; Claes, Karolien; Van Immerseel, Filip; Verbeke, Kristin; Ferrante, Marc; Verhaegen, Jan; et al.
Abstract : Objective: Bacteria play an important role in the onset and perpetuation of intestinal inflammation in inflammatory bowel disease (IBD). Unlike in Crohn's disease (CD), in which dysbiosis has been better characterised, in ulcerative colitis (UC), only small cohorts have been studied and showed conflicting data. Therefore, we evaluated in a large cohort if the microbial signature described in CD is also present in UC, and if we could characterise predominant dysbiosis in UC. To assess the functional impact of dysbiosis, we quantified the bacterial metabolites. Design: The predominant microbiota from 127 UC patients and 87 age and sex-matched controls was analysed using denaturing gradient gel electrophoresis (DGGE) analysis. Differences were quantitatively validated using real-time PCR. Metabolites were quantified using gas chromatography–mass spectrometry. Results: Based on DGGE analysis, the microbial signature previously described in CD was not present in UC. Real-time PCR analysis revealed a lower abundance of Roseburia hominis (p<0.0001) and Faecalibacterium prausnitzii (p<0.0001) in UC patients compared to controls. Both species showed an inverse correlation with disease activity. Short-chain fatty acids (SCFA) were reduced in UC patients (p=0.014), but no direct correlation between SCFA and the identified bacteria was found. Conclusions: The composition of the fecal microbiota of UC patients differs from that of healthy individuals: we found a reduction in R hominis and F prausnitzii, both well-known butyrate-producing bacteria of the Firmicutes phylum. These results underscore the importance of dysbiosis in IBD but suggest that different bacterial species contribute to the pathogenesis of UC and CD.